TOTAL QUALITY MANAGEMENT DALAM SISTEM MANAJEMEN BERBASIS MADRASAH DI SMP - M. Saifuddin Al-Huda; Mudzakkir Ali; Nur Cholid; Ifada Retno Ekaningrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Efforts to improve the quality of education are a continuous process that requires constant innovation to prevent educational institutions from stagnating amidst increasingly competitive global competition. This study aims to analyze the implementation of Total Quality Management (TQM) at Sirojuttholibin Pegandon Kendal Middle School, focusing on leadership, continuous improvement, quality standard setting, and customer relationship management. Using a qualitative approach with field study methods through observation, in-depth interviews, and documentation, this study examines the managerial stages that are systematically implemented. The findings indicate that the principal applies democratic leadership through a bottom-up decision-making mechanism that is effective in increasing participation and a sense of ownership of all components of the madrasah. The quality improvement strategy is implemented through the PDCA (Plan-Do-Check-Act) cycle to ensure regular evaluation and rapid corrective action on operational constraints. Quality standards are realized through student-centered learning methods and optimization of infrastructure that supports active interaction. As supporting data for the effectiveness of TQM, the integration of digital applications has been proven to boost the average learning achievement score by up to twenty percent. Customer relationships are also strengthened through strategic collaborations with the business world and external training institutions. The main conclusion confirms that consistent implementation of TQM has succeeded in transforming madrasah management to be more professional, responsive to change, and able to fulfill customer satisfaction holistically in order to produce competitive graduates according to the demands of the times. ABSTRAK Upaya peningkatan mutu pendidikan merupakan proses berkesinambungan yang menuntut inovasi konstan agar lembaga pendidikan tidak mengalami stagnasi di tengah persaingan global yang semakin kompetitif. Penelitian ini bertujuan untuk menganalisis penerapan Total Quality Management (TQM) di SMP Sirojuttholibin Pegandon Kendal dengan fokus pada kepemimpinan, perbaikan berkelanjutan, penetapan standar kualitas, dan manajemen hubungan pelanggan. Menggunakan pendekatan kualitatif dengan metode studi lapangan melalui teknik observasi, wawancara mendalam, dan dokumentasi, penelitian ini mengkaji tahapan manajerial yang diimplementasikan secara sistematis. Temuan menunjukkan bahwa kepala sekolah menerapkan kepemimpinan demokratis melalui mekanisme pengambilan keputusan bottom-up yang efektif dalam meningkatkan partisipasi serta rasa memiliki seluruh komponen madrasah. Strategi perbaikan mutu dijalankan melalui siklus PDCA (Plan-Do-Check-Act) untuk memastikan evaluasi berkala dan tindakan korektif yang cepat terhadap kendala operasional. Standar kualitas diwujudkan melalui metode pembelajaran berpusat pada siswa serta optimalisasi sarana prasarana yang mendukung interaksi aktif. Sebagai data pendukung efektivitas TQM, integrasi aplikasi digital terbukti mampu mendongkrak nilai rata-rata prestasi belajar hingga dua puluh persen. Hubungan pelanggan juga diperkuat melalui kolaborasi strategis dengan dunia usaha dan lembaga pelatihan eksternal. Simpulan utama menegaskan bahwa implementasi TQM yang konsisten berhasil mentransformasi manajemen madrasah menjadi lebih profesional, responsif terhadap perubahan, dan mampu memenuhi kepuasan pelanggan secara holistik demi menghasilkan lulusan kompetitif sesuai tuntutan zaman.